Analisis Deiksis dalam Cerpen Senyum Karyamin Karya Ahmad Tohari - Santi, Nelli Eka Diana; Utami, Sisilia Tri (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
This study aims to analyze and describe the use of deixis in literary works. Especially in the short story entitled "Senyum Karyamin". The researcher chose short stories as a source of data, namely, because short stories are more deixis found in them. This study is a qualitative study using a descriptive method. The data collection technique in this study is the reading and note-taking method. The collection tool used is people as the main instrument, and writing tools are used to take notes. The data analysis technique used in this study is to use interactive data analysis techniques. Sourced from data in the form of a short story entitled "Senyum Karyamin" by Ahmad Tohari. Based on the results of the study, there are five types of deixis in the short story "Senyum Karyamin", namely people (persona) there are 4 data, place 2 data, time 3 data, discourse 4 data, and social 2 data.